Inventory Management and Proactive Maintenance to Enhance Operational Efficiency in Excavators: Focus on Common Spare Parts Issues - Surojo; Setiawan, Widia; Harjono; Santosa, Nugroho; Winarto, Felixtianus Eko Wismo; Mandala, Wirawan Widya (Fakultas Teknik Universitas Pancasila, 2025)
Effective inventory management and maintenance are critical for the operational efficiency of heavy equipment such as excavators. This study focuses on optimizing spare parts inventory for Cummins diesel engines using the min-max stock method. It aims to improve inventory control by categorizing spare parts into slow-moving, medium-moving, and fast-moving components and addressing maintenance issues that impact performance. The research utilized the min-max stock method to determine optimal inventory levels, ensuring spare parts availability while minimizing holding costs. Key maintenance issues in components such as track shoes, cam shafts, rear shafts, motor starters, and exhaust manifolds were identified through inspections. Advanced diagnostic tools, including vibration analyzers and thermal imaging, were used for proactive maintenance. The study identified critical wear and damage in components like track shoes, cam shafts, and exhaust manifolds, which could lead to equipment failure if not addressed. Implementing the min-max stock method helped reduce stockouts and overstocking, ensuring an optimal balance in inventory. The results demonstrate that integrating the min-max stock method with systematic maintenance practices significantly improves operational efficiency. The use of real-time diagnostic tools enabled early issue detection, reducing downtime and maintenance costs. This study emphasizes the importance of inventory optimization, regular inspections, and timely maintenance interventions for enhancing equipment reliability. Future research should explore predictive maintenance technologies to further refine inventory and maintenance strategies in the heavy equipment sector.